Skull bone marrow and skull meninges channels: redefining the landscape of central nervous system immune surveillance - Liang Liu; Xian Zhang; Yan Chai; Jianning Zhang; Quanjun Deng; Xin Chen (Cell Death and Disease)
Abstract The understanding of neuroimmune function has evolved from concepts of immune privilege and protection to a new stage of immune interaction. The discovery of skull meninges channels (SMCs) has opened new avenues for understanding central nervous system (CNS) immunity. Here, we characterize skull bone marrow and SMCs by detailing the anatomical structures adjacent to the skull, the differences between skull and peripheral bone marrow, mainstream animal processing methods, and the role of skull bone marrow in monitoring various CNS diseases. Additionally, we highlight several unresolved issues based on current research findings, aiming to guide future research directions.